The contribution of agriculture to growth: Colombia - Berry, Albert (International Food Policy Research Institute, 1995)
As a perusal of Colombia's economic history makes clear, agriculture has been central to the economy's generally satisfactory performance. Agriculture's postwar growth rate (3.7 percent over 1950-80) was well above the average for developing countries and was unusually high in relation to the growth rate of GDP (5.1 percent over 1950-80). During the years of fastest GDP growth (5.9 percent in 1965-80), agriculture grew at 4.5 percent, which was somewhat higher than its longer-period average. This chapter therefore gives special attention to the latter period.